Nerve Growth Factor Interactions with Mast Cells. (January 2014) - Kritas, S.K.; Caraffa, A.; Antinolfi, P.; Saggini, A.; Pantalone, A.; Rosati, M.; Tei, M.; Speziali, A.; Saggini, R.; Pandolfi, F.; Cerulli, G.; Conti, P.
Neuropeptides are involved in neurogenic inflammation where there is vasodilation and plasma protein extravasion in response to this stimulus. Nerve growth factor (NGF), identified by Rita Levi Montalcini, is a neurotrophin family compound which is important for survival of nociceptive neurons during their development. Therefore, NGF is an important neuropeptide which mediates the development and functions of the central and peripheral nervous system. It also exerts its proinflammatory action, not only on mast cells but also in B and T cells, neutrophils and eosinophils. Human mast cells can be activated by neuropeptides to release potent mediators of inflammation, and they are found throughout the body, especially near blood vessels, epithelial tissue and nerves. Mast cells generate and release NGF after degranulation and they are involved in iperalgesia, neuroimmune interactions and tissue inflammation. NGF is also a potent degranulation factor for mast cells in vitro and in vivo, promoting differentiation and maturation of these cells and their precursor, acting as a co-factor with interleukin-3. In conclusion, these studies are focused on cross-talk between neuropeptide NGF and inflammatory mast cells.